Detection of Mitochondrial DNA Mutations in Nonmuscle Invasive Bladder Cancer - GÜNEY, AHMET İLTER; ULUCAN, KORKUT (MARY ANN LIEBERT INC, 2012)
Background: Mitochondrial DNA (mtDNA) mutations have been recently described in various tumors; however, data focusing on bladder cancer are scarce. To understand the significance of mtDNA mutations in bladder cancer development, we investigated the mtDNA alterations in bladder cancer cases. Methods: We studied the mtDNA in 38 bladder tumors and 21 microdissected normal bladder tissue samples. Mitochondrial genes ATPase6, CytB, ND1, and D310 region were amplified by polymerase chain reaction and then sequenced. Results: We detected 40 mutations in our patient population. Our findings indicate that G8697A, G14905A, C15452A, and A15607G mutations are frequent in bladder cancers (p < 0.05). In addition, the incidence of A3480G, T4216C, T14798C, and G9055A mutations were higher in patients with bladder tumors. Conclusions: In conclusion, the high incidence of mtDNA mutations in bladder cancer suggests that mitochondria could play an important role in carcinogenesis and mtDNA could be a valuable marker for early bladder cancer diagnosis.
Keywords: MONONUCLEOTIDE REPEAT; BREAST-CANCER; TUMORS; GENOME; IDENTIFICATION; PATHWAYS; PROSTATE; TARGET; RISK